ACETONE CYANOHYDRIN (ACH) ACCIDENT PREVENTION AND CONSEQUENCES OF ELIMINATION PROBLEM - Zarecka, Diāna; Noviks, Gotfrīds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
Environmentally hazardous chemical emergency nowadays is a topical problem which cannot be avoided but that it is possible to do away with the least possible damage to the environment. Considered the situation in Kundzinsala where a 23-ton tank with acetone cyanohydrin began an uncontrollable chemical reaction. Described as crash liquidated.